2018
DOI: 10.1002/mrm.27620
|View full text |Cite
|
Sign up to set email alerts
|

Integrated multi‐echo denoising strategy improves identification of inherent language laterality

Abstract: Purpose Although increasingly used in both neuroscience and clinical studies, a major challenge facing resting‐state FMRI (rs‐FMRI) still lies in isolating BOLD signal fluctuations resulting from neuronal activity from noise. In this study, we investigated the effect of a newly proposed denoising approach, integrated multi‐echo rs‐FMRI analysis, on language mapping. Methods Multiband multi‐echo rs‐FMRI data were acquired, along with language task FMRI that identified language areas in the left hemisphere of 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
(84 reference statements)
1
9
0
Order By: Relevance
“…In an attempt to minimize the contribution of such nuisance factors to our resting data—which is more strongly affected by these undesired sources of fluctuation—we used a ME‐ICA denoising strategy previously shown to improve identification of intrinsic connectivity networks in resting state fMRI (Kundu et al, 2012; Kundu et al, 2013). In fact, one recent study found that while apparent left‐hemisphere language network dominance was seen across several processing approaches, laterality index values were higher when using an integrated ME processing approach (Amemiya, Yamashita, Takao, & Abe, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In an attempt to minimize the contribution of such nuisance factors to our resting data—which is more strongly affected by these undesired sources of fluctuation—we used a ME‐ICA denoising strategy previously shown to improve identification of intrinsic connectivity networks in resting state fMRI (Kundu et al, 2012; Kundu et al, 2013). In fact, one recent study found that while apparent left‐hemisphere language network dominance was seen across several processing approaches, laterality index values were higher when using an integrated ME processing approach (Amemiya, Yamashita, Takao, & Abe, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Collecting more echoes opens up the possibility of applying ICA and classifying independent components into BOLD-related or noise, an approach known as multi-echo independent component analysis (ME-ICA) ( Kundu et al, 2013 , 2012 , 2017 ). Compared to single-echo data denoising, ME-ICA can improve the mapping of task-induced activation ( Amemiya et al, 2019 ; DuPre et al, 2016 ; Evans et al, 2015 ; Gonzalez-Castillo et al, 2016 ; Lombardo et al, 2016 ). It also outperforms single-echo ICA-based denoising of resting-state fMRI data ( Dipasquale et al, 2017 ), which is particularly beneficial to obtain more reliable functional connectivity mapping in individual subjects ( Lynch et al, 2020 ) and in brain regions with reduced signal-to-noise ratio, such as the basal forebrain ( Markello et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…independent of TE, related to non-BOLD fluctuations in the net magnetization Δ ρ ), an approach known as multi-echo independent component analysis (ME-ICA) (Kundu et al, 2013(Kundu et al, , 2012(Kundu et al, , 2017. Compared to single-echo data denoising, ME-ICA can improve the mapping of task-induced activation (DuPre, Luh, & Spreng, 2016;Gonzalez-Castillo et al, 2016;Lombardo et al, 2016), for example in challenging paradigms with slow-varying stimuli (Evans, Kundu, Horovitz, & Bandettini, 2015) or language mapping and laterality (Amemiya, Yamashita, Takao, & Abe, 2019). It also outperforms single-echo ICA-based denoising of restingstate fMRI data (Dipasquale et al, 2017), which is particularly beneficial more efficient and reliable functional connectivity mapping in individual subjects (Lynch, Power, Dubin, Gunning, & Liston, 2020) and in brain regions where traditional single-echo acquisitions offer reduced signal-to-noise ratio, such as the basal forebrain (Markello, Spreng, Luh, Anderson, & De Rosa, 2018).…”
Section: Introductionmentioning
confidence: 99%